The Tumor Border Configuration of Colorectal Cancer as a Histomorphological Prognostic Indicator - Koelzer, Viktor H.; Lugli, Alessandro (Frontiers in Oncology, 2014)
Histomorphological features of colorectal cancers (CRC) represent valuable prognostic indicators for clinical decision making. The invasive margin is a central feature for prognostication shaped by the complex processes governing tumor-host interaction. Assessment of the tumor border can be performed on standard paraffin sections and shows promise for integration into the diagnostic routine of gastrointestinal pathology. In aggressive CRC, an extensive dissection of host tissue is seen with loss of a clear tumor-host interface. This pattern, termed “infiltrative tumor border configuration” has been consistently associated with poor survival outcome and early disease recurrence of CRC patients. In addition, infiltrative tumor growth is frequently associated with presence of adverse clinicopathological features and molecular alterations related to aggressive tumor behavior including BRAFV600 mutation. In contrast, a well demarcated “pushing” tumor border is seen frequently in CRC cases with low risk for nodal and distant metastasis. A pushing border is a feature frequently associated with mismatch-repair (MMR) deficiency and can be used to identify patients for molecular testing. Consequently, assessment of the tumor border configuration as an additional prognostic factor is recommended by the AJCC/UICC to aid the TNM-classification. To promote the assessment of the tumor border configuration in standard practice, consensus criteria on the defining features and method of assessment need to be developed further and tested for inter-observer reproducibility. The development of a standardized quantitative scoring system may lay the basis for verification of the prognostic associations of the tumor growth pattern in multivariate analyses and clinical trials. This article provides a comprehensive review of the diagnostic features, clinicopathological associations and molecular alterations associated with the tumor border configuration in early stage and advanced CRC.